Orthogonal En/Decoders for Truly Asynchronous Spectral Amplitude Encoded OCDMA - Huiszoon, B.; Bakker, L.; de Waardt, H.; Khoe, G.D.; Fledderus, E.R.; Koonen, A.M.J. (2007 IEEE International Conference on Communications, 2007)
In this paper, theoretical results are presented on the modular construction of orthogonal tree and cascade encoders/decoders of any size for truly asynchronous and cost-efficient spectral amplitude encoded OCDMA on a passive optical network. Three modular building blocks are proposed and described in detail. The tree structure is introduced that enables parallel code processing with a single device. The orthogonality of the code set is evaluated whereafter a revised construction method is proposed. Analysis and simulation confirm that a tree constructed via this method is orthogonal.